Anti-Inflammatory Activity of Ethanol Extract of Cashew Stem Bark (Annacardium Occidentale L.) on Rat Paw Edema Induced by Carrageenan - Harsini, Harsini; Sutardja, Iwa; Martono, Sudibyo; Sunarintyas, Siti; Sudarsono, Sudarsono (The Indonesian Journal of Dental Research)
Introduction: Cashew stem bark (Anacardium occidentale L.) was traditionally used to cure inflammation in the oral cavity. Phenolic substances such as phenol and anacardic acid that have anti-inflammatory effect was found in cashew stem bark. The aim of this study was to investigate the anti-inflammatory activity of the ethanol extract of cashew stem bark and indometazine as Non-steroid anti-inflammatory drug. Materials and Methods: Cashew stem bark was collected from Faculty of Dentistry, Universitas Gadjah Mada, Yogyakarta, Indonesia. Extraction was done by maceration method using ethanol as solvent. Anti-inflammatory activity of 40 mg/kg bw, 80mg/kg bw, 160mg/kg bw dosage of cashew stem bark extract was monitored and indometazine 10 mg/kg bw was used as positive control. Edema volume determination on rat paw was counted as area under cure (AUC) value and anti-inflammatory percentage. Result: This study result showed that total phenolic content on cashew stem bark was 12.25 Â± 0.26% w/w gallic acid equivalent (GAE). The anti-inflammatory activity of cashew stem bark extract in this study were 9.985Â±6.483% for 40mg/kg BW, 15.576Â±6.754% for 80mg/kg bw, 25.87Â±19.7% for 160mg/kg bw and 56.85 Â±15.52% for Indometazine 10 mg/kg bw. Analysis of Variance (ANOVA) method was applied on the results and showed significant anti-inflammatory activity of ethanol extract on cashew stem bark (p<0.05). Conclusion: In conclusion, ethanol extract of cashew stem bark has anti-inflammatory activity. However, itsâ activity is lower than indometazine.